2014
DOI: 10.1007/s12032-014-0974-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of LAPTM4B is correlated with tumor angiogenesis and poor prognosis in non-small cell lung cancer

Abstract: Lysosome-associated protein transmembrane-4 beta (LAPTM4B) is a novel oncogene, which has been indicated to be dramatically overexpressed in various malignant tumors. The aims of this study were to detect LAPTM4B protein expression in patients with non-small cell lung cancer (NSCLC) and then analyze the relationships of LAPTM4B protein with clinicopathologic factors, tumor angiogenesis and prognosis with SPSS statistical software. Immunohistochemistry was used to examine the expression of LAPTM4B and CD34 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Tang et al examined LAPTM4B and CD34 proteins in non-small cell lung cancer, and their results revealed that LAPTM4B might promote tumor progression by inducing tumor angiogenesis [24]. Meng et al indicated that the downregulation of LAPTM4B suppressed tumor migration and invasion and significantly decreased VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al examined LAPTM4B and CD34 proteins in non-small cell lung cancer, and their results revealed that LAPTM4B might promote tumor progression by inducing tumor angiogenesis [24]. Meng et al indicated that the downregulation of LAPTM4B suppressed tumor migration and invasion and significantly decreased VEGF expression.…”
Section: Discussionmentioning
confidence: 99%
“…In tumors, it appears to play an oncogenic role. High LAPTM4B levels are associated with poor prognosis in many types of cancers (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41), and in vitro and in vivo analyses of cells in which LAPTM4B was overexpressed or silenced indicate that LAPTM4B favors proliferation, migration, invasion, tumorigenesis, and metastasis (42,43). Two mechanisms by which LAPTM4B plays oncogenic roles have recently been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor growth relies on new blood vessels. Tang et al have reported that the LAPTM4B protein is closely associated with progression and micro vessel density in the context of non-small cell lung cancer, suggesting that LAPTM4B could play an important role in tumor angiogenesis [10]. However, the exact study, an LAPTM4B blockade may play a direct role in the degradation of HIF-1 and the …”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 96%